Dynamical Properties of Epoxy–Chopped Rock Wool Composites - Kadhum, Ali Qasim; Al - Ajaj, E A A (Al-Nahrain Journal of Science, 2018)
Hand- lay up method was used to prepare epoxy (EP) – chopped rock wool composites. The dynamical properties for EP/chopped rock wool composites with different weight percentage of chopped rock wool (2.5, 3.5, 5, 7.5, and 10 wt %) had been studied by using ultrasonic test method (direct method).Ultrasonic test as a non destructive testing become widely used in industry and reliable measurements, ultrasonic is the study of sound waves of frequencies higher than the upper hearing limit of the human ear (frequency region above 20 kHZ).A local apparatus according to ASTM C167-82 was prepared to measure the thickness for loose materials to calculate the density of materials like rock wool.A new sonic viewer device was used to measure the average times of compressional and shear waves(Tp,Ts) respectively which are transit through the composites to calculate their velocities (Vp,Vs)  in order  to calculate the dynamic elastic moduli such as  Poisson ratio (μ), Shear modulus (G), Modulus of elasticity (E), Bulk modulus (B), and other parameters such as acoustic impedance (Z) for all composites.It was shown that random values of compressional velocity (Vp) were observed for EP/chopped rock wool composites due to random distribution of chopped rock wool which could be as a results of weak interface bond between EP and chopped rock wool.  Shear velocity (Vs) values are decreased with increasing weight percentage of chopped rock wool and less than Vp values due to the particles of material are vibrating perpendicular to the direction of shear waves propagation. Slight variation of poisson ratio μ, and bulk modulus B for all composites with increasing weight percentage of chopped rock wool. Larger variation of shear modulus G, and   modulus of elasticity E values for EP/chopped rock wool composites due to defects such as voids and weak interface bond, G values decrease with increasing weight percentage of rock wool as a result of decreasing shear velocity values. Almost similar values of acoustic impedance Z are observed and lie between 3.57 to 3.93×106 kg/m2sec for all composites.